Differences in the result of MC Namara cephalometric analysis before and after protrusive bimaxillary class I malocclusion treatment: Research as descriptive - Soegiharto, Eko Poetranto; Evangelina, Ida Ayu; Mardiati, Endah; Laviana, Avi (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Bimaxillary protrusive has characteristics are convex profile, class 1 molar relation, protrusive maxillary and mandibular incisors. Extraction of four maxillary and mandibular first premolar teeth is a treatment option. Mc Namara cephalometric analysis was used to evaluate the variables of soft tissue and hard tissue variables in the sagittal and vertical directions thoroughly. The aim of this study was to measure the differences before and after treatment bimaxillary protrusive class I malocclusion treatment accompanied by extraction of four first premolars at the PPDGS Orthodontic Clinic FKG UNPAD with Mc Namara cephalometry analysis. Methods: This research is a descriptive comparative analytic study. Samples are lateral cefalograms before and after treatment as many as 15 bimaxillary protrusive class I malocclusion patientst, which were taken by purposive sampling method, the data processed and analyzed by paired t-test. Results: Variable upper lip canting (p<0.05), mandibular plane angle (p<0.05), maxillary incisor to point A distance (p<0.05), mandibular incisor to APog distance. (p<0.05) indicates a significanting difference. Variable nasolabial angle p>0.05), point A to N perpendicular (p>0.05), condylion to point A (p>0.05), condylion to gnation (p>0.05), LAFH (p>0.05), facial axis angle (p> 0.05), pogonion to N perpendicular (p>0.05) indicates an insignificanting difference. Conclusions: Significanting differences before and after treatment seen in mandibular plane angle, maxillary incisor distance to point A, mandibular incisor distance to Apog, upper lip cantinging. Meanwhile nasolabial angle, point A to N perpendicular, condylion to point A, condylion to gnation, facial axis angle, pogonion to N perpendicular showed insignificanting results.KEY WORDS: protrusive, incisive, cephalometry, analysisPerbedaan hasil analisis sefalometri McNamara sebelum dan sesudah perawatan maloklusi kelas I protrusif bimaksilerABSTRAKPendahuluan: Protrusif bimaksiler mempunyai karakteristik profil konveks, relasi molar kelas 1, insisif rahang atas dan bawah protrusif. Ekstraksi empat gigi premolar rahang atas dan bawah menjadi pilihan perawatan. Analisis Mc Namara mengevaluasi variabel jaringan lunak, keras dalam arah sagital dan vertikal secara menyeluruh. Tujuan penelitian ini untuk mengukur perbedaan hasil analisis sefalometri Mc Namara sebelum dan sesudah perawatan maloklusi kelas I protusif bimaksiler dengan pencabutan empat premolar rahang atas dan bawah di Klinik PPDGS Ortodonti FKG UNPAD. Metode: Penelitian bersifat deskriptif analitik komparatif. Sampel berupa sefalogram lateral sebelum dan sesudah perawatan dari 15 pasien maloklusi kelas I protrusif bimaksiler yang dirawat dengan ekstraksi empat gigi premolar rahang atas dan rahang bawah di klinik PPDGS FKG UNPAD, diambil dengan metode purposive sampling, diolah dan dianalisis dengan t-test berpasangan. Hasil: Variabel canting bibir atas (p<0,05), sudut bidang mandibula (p<0,05), jarak insisif RA ke titik A (p<0,05) dan jarak insisif RB ke APog (p<0,05) menunjukkan perbedaan signifikan. Pengukuran variabel sudut nasolabial (p>0,05), titik A terhadap N perpendicular (p>0,05), condylion ke titik A (p>0,05), condylion ke gnation (p>0,05), LAFH (p>0,05), facial axis angle (p>0,05) dan pogonion ke N perpendicular (p>0,05) menunjukkan hasil yang tidak signifikan. Simpulan: Terdapat perbedaan analisis Mc Namara sebelum dan sesudah perawatan pada sudut bidang mandibula, jarak insisif atas ke titik A, jarak insisif bawah ke APog, cantinging bibir atas. Tidak terdapat perbedaan pada titik A terhadap N perpendicular, condylion ke titik A, condylion ke gnation, pogonion ke N perpendicular, sudut nasolabial dan facial axis angle.KATA KUNCI: protrusif, insisif, ekstraksi, sefalometri, analisis